KEMAMPUAN MAHASISWA DALAM MENGANALISIS PUISI “ULAT” KARYA OKA RUSMINI MELALUI PENDEKATAN FEMINIS - Deviana Rahmalia Putri; Fajrina Nur Azizah; Wardatun Nikoyah; Kusuma, Dewi Kusuma (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2023)
This study examines the ability of students in the city of Cirebon to analyze poetry with feminism in it. The poem that was used as the object of the research was a poem entitled "Ulat" by Oka Rusmini. Through this poem, Oka Rusmini has inspired the fighting spirit of women who are intimidated to be able to stand up and fight for their rights in society. This study uses a feminist approach. The method used in this research is descriptive qualitative method. The results showed that the students' ability to analyze the poem "Ulat" by Oka Rusmini was not good enough, because the students did not know the meaning behind the poem.